STATINS AND THE RISK OF DIABETES MELLITUS - O. M. Drapkina (Столичная издательская компания, 2015)
Randomized controlled trials have clearly demonstrated the efficacy of statins in reduction of serum low density lipoprotein cholesterol level by 25-50% from the baseline. Statins may increase the risk of diabetes mellitus (DM) in long-term therapy and use of high doses. Diabetogenic action is statins class effect and does not depend on their hydrophobic or hydrophilic properties. However, the use of statins in patients with DM is obligatory. The statins diabetogenic  risk is exaggerated and we will continue to treat our patients with statins.